Functional characteristics of microcirculation and their prognostic value in patients with arterial hypertension - A. P. Vasilyev; N. N. Streltsova; M. A. Sekisova; M. V. Malishevskyi; I. V. Samoylova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study functional characteristics of microcirculation (MC), various hemodynamic variants of peripheral hemocirculation, and their clinical and prognostic value in patients with arterial hypertension (AH). Material and methods. The study included 78 AH patients (mostly with Stage II-III AH) and 29 healthy individuals. Forearm skin MC was assessed by laser Doppler flowmetry. Results. In AH patients, substantially elevated pre-capillary tone resulted in reduced nutritive blood flow, increased total peripheral vascular resistance, arteriolovenular shunting, and venous hyperemia. The depression of the main MC regulatory mechanisms was partly compensated by passive, breath and pulse-related factors. Conclusion. Among all hemodynamic MC types, the negative effects on target organs and prognosis were maximal for spastic and congestive-stasic MC variants. MC types should be taken into account when choosing optimal strategy of pharmaceutical treatment.